مفهوم الدولة وضرورة وجودها في ضوء القرآن الكريم والواقع المعاصر = The concept of state and its necessary existence in light of the noble Qur’an and the present reality - Elatrash, Radwan Jamal Yousef; Shousha, Hossam Moussa (Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), International Islamic University Malaysia, 2018)
يركز هذا البحث على بيان مفهوم الدولة من خلال استنباط معانٍ دالة على ضرورة وجودها انطلاقاً من القرآن الكريم والواقع المعاصر، وتكمن مشكلة البحث في أن المفكرين الإسلاميين القدامى -حسب اطلاع الباحث- لم يتناولوا الدولة بالمفهوم الحديث كما في الفكر الغربي. ذلك أن الدولة رمز للنظام والقانون، والحياة لا تستقيم إلا بهما، كذلك يركز هذا البحث على الاختلاف بين الفكر السياسي الإسلامي ونظيره الغربي في فهم وتعريف الدولة، حيث تختلف الثقافات والقناعات بين الاتجاهين، وذلك من خلال استخدام المنهج الاستقرائي والمنهج التحليلي. وقد أثبت البحث من خلال إبراز أهم النتائج أن الدولة مرتبطة بالحياة، لا غنى عنها للحياة الكريمة والعدالة الاجتماعية المتوازنة في كل مرافق الحياة وخصوصاً السياسية والقانونية. **************************************************** This research focuses on elucidating the concept of state through deducing conceptions that indicate its necessary existence, and that being from the Qur’ānic perspective as well as the present reality. The research problem lies in the fact that the traditional Islamic thinkers – according to the researcher’s knowledge – did not discuss the state as a modern concept as in Western thought. This is because the state is a symbol of system and law, without which life cannot proceed properly. Also, this research highlights the difference between Islamic political thought and its Western counterpart in understanding and defining the state, as the two trends differ in culture and conviction; this was done using an inductive and analytical methodology. Highlighting the most significant results, the research proved that the state is closely connected to life, and cannot be done without for providing a good life and balanced social justice in all aspects of life, especially the political and legal.